Analisis Persepsi Sosial Mahasiswa dan Dosen Ilmu Hukum Universitas Pendidikan Indonesia Terhadap RUU Perampasan Aset - Adam Sultan Fatah; Muhammad Haikal Assady; Muhammad Kaysan Dhiya’ulhaq; RD. Elang Fela Stanislaus Putra Pratama (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This research aims to analyze the social perceptions of students and lecturers in the Legal Sciences Study Program at the Indonesian Education University regarding the Asset Confiscation Bill. The method used is a qualitative approach with data collection techniques through in-depth interviews with three students and three lecturers. The research results show that both students and lecturers generally support the urgency of passing the bill as an effort to eradicate corruption and recover state losses. However, there are concerns about the potential for abuse of authority and lack of transparency in its implementation. Respondents emphasized the importance of independent oversight, reform of law enforcement institutions, and public education to increase understanding and trust in this bill. This research recommends that the legislative process be carried out in a participatory and accountable manner to ensure the effectiveness and legitimacy of the law in its implementation.